Design and development of atypical multicopter with application of tricopter - Wong, Zhuo Wei (2015)
Multicopter is a vertical takeoff and landing unmanned aerial vehicle (UAV). Due to technological advances, low cost flight controller is available for general public to design and develop their own multicopter. However, odd rotor configuration multicopters are less commonly seen due to their unbalanced torque around the yaw axis. Thus, this project aims to explore the flight characteristic of a tricopter. The tricopter is built and tested for its flight stability. The control system in the flight controller is analyzed and parameters were adjusted to improve the flight performance of the tricopter. Autonomous flight navigation was carried out on the tricopter for potential military applications.